ALAT TES PSIKOLOGI KONTEKS INDONESIA: TANTANGAN PSIKOLOGI DI ERA MEA - Suwartono, Christiany (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2016)
Abstract — Currently, Indonesia is entering the era of the ASEAN Economic Community (AEC), a golden opportunity and a challenge to be able to identify the potential of the nation in order to become an important player in the ASEAN region and even the world. A solution to face this challenge is through the trustworthy  and  reliable psychological tests. Unfortunately in Indonesia, the realization becomes hard as the given attention and effort for the test development in the Indonesian context are little. The version of available tests are very far behind from the original version, in both content and standardization. In addition, the test questions have been leaked and relatively accessible to public. As the result, the scores obtained from these tests  become  questionable, mainly in terms of the validity. One of the efforts to renew the tests is through test adaptation. In order to ensure the validity of the test adaptation results, International Test Commission has issued guidance on the adaptation process of the test. The intention is for the adapted test to be as beneficial as its original version. The other effort is by making novel tests according to the context and needs on the practice area. Good cooperation between the different occupation should also be prioritized and strengthened in order to provide the availability of valid and reliable tests.Abstrak — Saat ini Indonesia sedang memasuki era Masyarakat Ekonomi ASEAN (MEA). Hal ini merupakan suatu kesempatan emas sekaligus tantangan untuk lebih bisa mengidentifikasi potensi bangsa agar dapat memberikan kontribusi di wilayah ASEAN, bahkan dunia. Salah satu hal yang dapat mewujudkan hal tersebut adalah dengan adanya alat tes psikologi yang handal dan terpercaya. Sayangnya di Indonesia, realisasi hal ini terhambat karena upaya yang diberikan pun sedikit. Alat tes yang tersedia sudah tertinggal jauh dari versi aslinya, baik secara isi maupun standarisasinya. Ditambah lagi, beredarnya bocoran soal-soal tes yang dapat diakses oleh masyarakat awam. Hal ini membuat validitas sekor yang diperoleh dipertanyakan. Upaya untuk memperbaharui tes-tes tersebut dapat dilakukan dengan cara adaptasi tes. International Test Comission mengeluarkan panduan mengenai adaptasi tes untuk menjamin validitas hasil adaptasi sebuah tes tertentu. Hal ini dilakukan agar tes yang diadaptasi tetap memiliki nilai manfaat yang memadai. Upaya lain yang dapat dilakukan adalah dengan membuat alat tes sendiri yang tujuannya sudah disesuaikan dengan konteks serta kebutuhan lapangan. Terjalinnya kerja sama yang baik dalam pekerjaan sebaiknya semakin diutamakan, guna tersedianya tes yang reliabel dan valid.